THE SCIENTIFIC AND SPIRITUAL HERITAGE OF UZBEK MUSICAL INSTRUMENTS. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is about the origin of Uzbek folk instruments, the sources of information about them, and the opinions of our scholars about Uzbek folk instruments in their musical treatises. The article also talks about the history of musical instruments and their importance today.